A.MU.C., Archivio Multimediale del Contemporaneo: il caso Anita Sieff: Ordine di senso (Mantichora. Italian Journal of Performance Studies, 2020)
The Multimedia Archive of Contemporary Art (A.Mu.C) is one of the experimental projects of my PhD research, which among its objectives aims to identify new professional skills and improving the means of fruition of the cultural assets in contemporary Venice .The project was developed for educational-outreach purposes, but it was proven to have a transversal nature, because it deals with sensitive aspects of many disciplines in several research areas. For the occasion, I will focus on the educational aspect of the project: inclusion of audio visual materials within the temporary exhibitions, using as an example the experience of the solo exhibition of Anita Sieff, Ordine di Senso curated by Chiara Bertola at Fondazione Querini Stampalia in Venice, Anita Sieff. Creazione di Senso. A.Mu.C aims to document, present and then edit an appropriate selection of the shot material, and ultimately filing in archives, the “making of” process of the exhibition.